Review Artikel: Pemanfaatan Kimia Komputasi Dengan Berbagai Metode Dalam Menentukan Desain Senyawa Baru - Lina Nurfadhila; Diah Muldianah; Diany Aprillia Nurdimayanthi; Dinda Shafira Rahmawati; Hajar Hartati; Hana Fadhilah (Journal of Pharmaceutical and Sciences, 2023)
Research in the pharmaceutical field is helped by the development of technology and science, one of which is in the field of medicinal chemistry related to drug discovery and treatment development design. Computation is one of the techniques in drug development with molecular docking and Quantitative Structure Activity (HKSA) methods which include synthesis, purification, design, identification and activity testing of a compound. The method used is to conduct studies from various sources with a total of 29 journals found on various official websites and which are used as the main journal as many as 10 journals with various computational techniques, namely molecular docking, PM3 semiempirical, AM1 semiempirical, in silico and HKSA. The potential of compounds from various literatures results in several medicinal purposes, namely as anticancer, antimalarial, antibacterial, anti-HIV and covid prevention. The potential of these compounds is obtained from different chemical compounds. The compounds used in this journal include compounds derived from 1,3-dibenzolythiourea, quinine compounds, fluoroquinolone parent compounds, chalcone-derived compounds, kuwanon compounds and their derivatives, leonurin compounds and their derivatives, compounds derived from N-(Benzoil)-N'-phenylthiourea, Beta asaron-derived compounds, meisiindigo-derived compounds and quercetin compounds.